2017
DOI: 10.1002/we.2103
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a CFD model with a synchronized triple‐lidar system in the wind turbine induction zone

Abstract: A novel validation methodology allows verifying a CFD model over the entire wind turbine induction zone using measurements from three synchronized lidars. The validation procedure relies on spatially discretizing the probability density function of the measured free-stream wind speed. The resulting distributions are reproduced numerically by weighting steady-state Reynolds averaged Navier-Stokes simulations accordingly. The only input varying between these computations is the velocity at the inlet boundary. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…(1) to the measurements. That gives the value of a as a function of U ∞ , which we assume is equal to the velocity particularly dominant for the Siemens 2.3MW because it has a high local loading below rated wind speed, see Troldborg and Meyer Forsting (2017). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(1) to the measurements. That gives the value of a as a function of U ∞ , which we assume is equal to the velocity particularly dominant for the Siemens 2.3MW because it has a high local loading below rated wind speed, see Troldborg and Meyer Forsting (2017). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…EllipSys3D is an incompressible finite volume flow solver, initially developed by Sørensen (1994) and Michelsen (1992), which incorporates both RANS and LES models, and has different methods of representing a wind turbine. In this section, the RANS-AD method is discussed.…”
Section: Ellipsys3d Rans-admentioning
confidence: 99%
“…They showed that thrust is the major parameter governing the induction strength [32], and other turbine parameters, such as yaw, tilt, and rotor design, etc. [32][33][34]. and environmental characteristics including wind shear, atmospheric turbulence, and topography, etc.…”
Section: Introductionmentioning
confidence: 99%